Does a GLP-1 receptor agonist change glucose tolerance in patients treated with antipsychotic medications? Design of a randomised, double-blinded, placebo-controlled clinical trial. Issue 3 (25th March 2014) - Larsen, Julie Rask; Vedtofte, Louise; Holst, Jens Juul; Oturai, Peter; Kjær, Andreas; Corell, Christoph U; Vilsbøll, Tina; Fink-Jensen, Anders
Abstract : Background: Metabolic disturbances, obesity and life-shortening cardiovascular morbidity are major clinical problems among patients with antipsychotic treatment. Especially two of the most efficacious antipsychotics, clozapine and olanzapine, cause weight gain and metabolic disturbances. Additionally, patients with schizophrenia-spectrum disorders not infrequently consume alcohol. Glucagon-like peptide-1 (GLP-1) has shown to improve glycaemic control and reduce alcohol intake among patients with type 2 diabetes. Objectives: To investigate whether the beneficial effects of GLP-1 analogues on glycaemic control and alcohol intake, in patients with type 2 diabetes, can be extended to a population of pre-diabetic psychiatric patients receiving antipsychotic treatment. Methods and analysis: Trial design, intervention and participants: The study is a 16-week, double-blinded, randomised, parallel-group, placebo-controlled clinical trial, designed to evaluate the effects of the GLP-1 analogue liraglutide on glycaemic control and alcohol intake compared to placebo in patients who are prediabetic, overweight (body mass index ≥27 kg/m 2 ), diagnosed with a schizophrenia-spectrum disorder and on stable treatment with either clozapine or olanzapine. Outcomes: The primary endpoint is the change in glucose tolerance from baseline (measured by area under the curve for the plasma glucose excursion following a 4 h 75 g oral glucose tolerance test) to follow-up at week 16. The secondary endpoints include changes of dysglycaemia, body weight, waist circumference, blood pressure, secretion of incretin hormones, insulin sensitivity and β cell function, dual-energy X-ray absorption scan (body composition), lipid profile, liver function and measures of quality of life, daily functioning, severity of the psychiatric disease and alcohol consumption from baseline to follow-up at week 16. Status: Currently recruiting patients. Ethics and dissemination: Ethical approval has been obtained. Before screening, all patients will be provided oral and written information about the trial. The study will be disseminated by peer-review publications and conference presentations. Trial registration number: ClinicalTrials.gov: NCT01845259, EudraCT: 2013-000121-31.